In Vitro Study on Glucose Utilization Capacity of Bioactive Fractions of Houttuynia cordata in Isolated Rat Hemidiaphragm and Its Major Phytoconstituent - Manish Kumar; Satyendra K. Prasad; Siva Hemalatha (Advances in Pharmacological Sciences)
Objective. The whole plant of Houttuynia cordata has been reported to have potent antihyperglycemic activity. Therefore, the present study was undertaken to investigate the glucose utilization capacity of bioactive fractions of ethanol extract of Houttuynia cordata (HC) in isolated rat hemidiaphragm. Methods. All the fractions, that is, aqueous (AQ), hexane (HEX), chloroform (CHL), and ethyl acetate (EA), obtained from ethanol extract of H. cordata were subjected to phytochemical standardization use in quercetin as a marker with the help of HPTLC. Further, glucose utilization capacity by rat hemidiaphragm was evaluated in 12 different sets of in vitro experiments. In the study, different fractions from H. cordata as mentioned above were evaluated, where insulin was used as standard and quercetin as a biological standard. Results. Among all the tested fractions, AQ and EA significantly increased glucose uptake by isolated rat hemidiaphragm compared to negative control. Moreover, AQ fractions enhanced the uptake of glucose significantly (p<0.05) and was found to be more effective than insulin. Conclusions. The augmentation in glucose uptake by hemidiaphragm in presence of AQ and EA fractions may be attributed to the presence of quercetin, which was found to be 7.1 and 3.2% w/w, respectively, in both the fractions.